Use of Hyaluronic Acid as Adjuvant in Periodontal Therapy and Healing: a Bibliographic Review - Marcelo Fernando Armijos Briones; Cinthya Lisbeth Sinchiguano Moreano; Coralia de los Ángeles Ortega Medina (Medisur)
Hyaluronic acid is a natural non-sulfated polysaccharide of the glycosaminoglycan family, it can cause different responses in the body, the high molecular weight has anti-inflammatory, immunosuppressive and healing effects, while the low molecular weight has proinflammatory properties. Perform a synthesis of information on the properties of hyaluronic acid and its use as an adjuvant in the therapy of gingivitis, chronic periodontitis and periodontal healing to verify its therapeutic effect and benefits in the field of dentistry. A search was carried out according to the PRISMA guidelines in the Pubmed, Cochrane Library, Mendeley and Google Scholar databases, including a total of 22 studies, three related to gingivitis, fourteen related to chronic periodontitis and five related to periodontal healing. Hyaluronic acid applications, either in gel or spray, have an effective result in the use for the treatment of periodontal diseases with a high, low or medium significance both in clinical and microbiological parameters.